Pelatihan dan Bimbingan Teknis Penulisan Artikel Ilmiah Berbasis PTK Guru-Guru SMA N 1 Cepiring Kabupaten Kendal - Sulhadi Sulhadi; Siti Wahyuni; Teguh Darsono; Putut Marwoto (BERDAYA Indonesian Journal of Community Empowerment, 2024)
Based on communication with one of the teachers at SMA N 1 Cepiring, information was obtained that the teachers needed updated information regarding the implementation of Class Action Research (CAR) and wrote down the results in scientific articles. Most teachers still experience difficulties in writing scientific articles which in turn have an impact on hampering the career paths and ranks of teachers. The low percentage of publication of teacher's scientific work is partly due to the fact that teachers still do not know the procedures for writing scientific papers according to academic standards. In line with these matters, this community service activity aims to provide information about CAR and scientific article writing. The method used in this activity is in the form of training and technical guidance with material covering CAR reviews, tips for writing CAR-based articles, how to access journal websites, mentoring activities in writing articles, and guidelines for submitting articles to scientific journals/magazines. After participating in this activity, teachers' motivation in professional competence and self-development in academic qualifications, especially problems in CAR up to publication can increase.